Far from the Eyes, Close to the Heart? The Attitude of Kindergarten Teachers to Distance Learning in Kindergartens in Israel - Alezra, Fani (Rocznik Pedagogiczny, 2020)
The coronavirus pandemic has forced the world to deal with distance learning. This article discusses distance learning in the kindergartens in Israel from the perspective of kindergarten teachers. The research was carried out after the first wave of the virus, in March 2020, and its problems was: What is the attitude of the kindergarten teachers in Israel to distance learning? The research used a linear (differential semantic) questionnaire that measures the degree to which they agree with statements related to distance learning in the cognitive, behavioral, and emotional aspects. The questionnaire was filled out by 213 kindergarten teachers. The research attempts to conclude about the kindergar- ten teachers’ perception of distance learning.